Chemical Inhibition of JAK2 Mimics Genetic Ablation of Uterine Function of Leukemia Inhibitory Factor (Global Journal of Medical Research, 2016)
Uterine receptivity needs to be synchronized with embryonic development, so the blastocyst stage of the embryo can implant. Leukemia Inhibitory Factor (LIF) is an essential factor for implantation, which is involved in the initiation of the window of implantation. However, the process by which the LIF signal pathway is transduced in the uterine luminal epithelium (LE) that leads to uterine receptivity is not completely elucidated. We tested the ability of cellular signaling inhibitors to disrupt uterine support of the embryo. Only Tyrphostin-AG490, an inhibitor of Jak2, can interfere with LIF signaling. Not only can AG490 reduce phosphorylated STAT3 levels in isolated LE, but it also ablated implantation when injected into uterine lumen. Furthermore, AG490 treatment in wild-type animals mimics the consequences of genetic ablation of LIF that results in free floating hatched embryos, which are unable to implant. Our results support the notion that Jak2 is the sole Janus kinase to mediate LIF activation in LE, and the signaling pathways of cytokines can serve as contraception targets.
Keywords: leukemia inhibitory factor (LIF); implantation; janus kinase 2 (Jak2); tyrphostin; AG490; DMSO; signal transduction; contraception